Pectoralis major turnover flap based on thoracoacromial vessels for sternal dehiscence. Issue 2 (28th August 2019) - Goishi, Keiichi; Harada, Hiroshi; Keyama, Tsuyoshi; Tsuda, Tatsuya; Hashimoto, Ichiro
Abstract: Background: Reconstruction of long and deep sternal defects has been challenging. The pectoralis major can be used in the conventional turnover method that requires the internal thoracic vessel. We developed a new turnover pectoralis major flap based on thoracoacromial vessels. The purpose of this report is to present results from 14 patients. Methods: Fourteen patients with a mean age of 73.6 years (range, 53–83 years) who had sternal defects underwent reconstruction via this procedure. The defects were caused by mediastinitis and sternal osteomyelitis in six and eight patients, respectively. The internal thoracic artery (ITA) was harvested in two patients. The mean defect size was 2.4 × 15.5 cm (ranging 1–4.3 × 13–18 cm). After elevation of the lateral border of the muscle and ligation of the third to fifth perforators from ITA, the lateral side was turned over and the medial lower portion of the flap was additionally transplanted to the defect. Results: The mean flap size was 10.7 × 18 cm (ranging 9–13 × 15–21 cm). For 11 patients, defects healed without any complications. Discharge after flap reconstruction was observed in three patients, two of whom were managed using conservative treatments. Only one patient who needed additional debridement required transplantation of the contralateral pectoral major flap. Conclusions: This muscle flap is nourished primarily by the thoracoacromial vessel. The long length and large volume of the muscle flap could be successfully turned over with this procedure even in patients that had their internal thoracic artery sacrificed.